The moisture distribution in wall-to-floor thermal bridges and its influence on mould growth (UCL Open Environment, 2022)
Moisture in building envelopes increases the energy consumption of buildings and induces mould growth, which may be amplified within the area of thermal bridges due to their different hygrothermal properties and complex structures. In this study, we aimed to (1) reveal the moisture distribution in the typical thermal bridge (i.e., wall-to-floor thermal bridge, WFTB) and its surrounding area and (2) investigate the mould growth in a building envelope that includes both a WFTB and the main part of a wall, in a humid and hot summer/cold winter region of China (Hangzhou City). The transient numerical simulations which lasted for 5 years were performed to model the moisture distribution. Simulated results indicate that the moisture distribution presents significant seasonal and spatial differences due to the WFTB. The areas where moisture accumulates have a higher risk of mould growth. The thermal insulation layer laid on the exterior surface of a WFTB can reduce the overall humidity while uneven moisture distribution may promote mould growth and water vapour condensation.